Analysis of Julung Fish Sales and Fishermen's Income in Fokalik Village, North Sanana Sub-District (Islamic Economic Review) - Takim, Akbar (Manunggal Halim Jaya, 2025)
This study aims to analyze the sale of julung fish and its impact on the income of fishermen in Fokalik Village, Sanana Utara District, Kepulauan Sula Regency, from an Islamic economic perspective. The method used is field research with a qualitative approach, which allows for an in-depth understanding of the social and economic conditions of fishermen.The results show that a fair profit-sharing management system can improve the well-being of the group of fishermen. Although the fishery potential in this area is very large, fishermen still face challenges such as fluctuating fish prices, limited capital, and simple technology. This study also highlights the importance of applying the principles of Islamic economics in the management of marine resources, which not only focus on economic profits but also on environmental sustainability. By emphasizing justice and balance, this approach can help fishermen achieve income stability and improve their standard of living without damaging the marine ecosystem. These findings provide important insights for the development of more sustainable and inclusive fisheries policies in the coastal areas of Indonesia.